Analisis Integritas dan Komitmen serta Budaya Organisasi terhadap Prestasi melalui Etos Kerja di Lembaga Penjaminan Mutu Pendidikan (LPMP) Daerah Istimewa Yogyakarta - Efni Pebrianti (SMARTINDO, 2022)
Purpose of this article: This study aims to determine the relationship between integrity, commitment, and organizational culture to the work ethic of employees at LPMP D.I. Yogyakarta.Methodology: This research used saturated sampling.Result: The results of the study show that the higher the value of integrity and commitment shown in the work ethic, the higher the employee's performance